Foliar nutrition to Valencia late (Citrus sinensis (L.) Osbeck) orange and tangor Murcott (Citrus reticulata Blanco x Citrus sinensis (L.) Osbeck) trees with macronutrients - Alayón Luaces, Paula; Rodríguez, Víctor Antonio; Píccoli, Analia Beatriz; Chabbal, Marco Daniel; Giménez, Laura Itati; Martínez, Gloria Cristina (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The objective of this study was to analyze the effects of different doses of foliar fertilizers with macronutrients on 'Valencia late' sweet orange and 'Murcott' tangor. Field experiments were done during three seasons in commercial orchards in Corrientes, Argentina. On complete block designs with four replications and experimental plots of four trees. Tested treatments were: T1 control; T2 N (12%) 2 L. ha- 1; T3 N (12%) 4 L.ha-1; T4 N (9%) and P (2.6%) 2 L. ha-1; T5 N (9%) and P (2.6%) 4 L ha- 1; T6 N (9.3%), P (2.6%) and K (2.1%) 2 L.ha-1; T7 N (9.3%), P (2.6%) and K (2.1%) 4 L.ha-1; sprayed three times per season, at pre-flowering, full flowering and last summer sprouting. Leaf concentrations of N, P and K were determined in leaves of fruiting branches obtained in autumn. At harvest, total fruit production was measured and diameter, percentage of juice, soluble solids content, acidity and ratio were determined on a 40 fruits per plot sample. Variance analysis and Duncan test were performed. In 'Valencia late', compared to the control, all sprayed treatments increased P foliar concentration. Treatment T7 increased the yield 38.7% respect to T1, but fruits presented smaller diameter. In 'Murcott', the fertilizer treatments increased fruit yield compared to the control, with higher production in T7 (64.9% upper) and T6 (43.8% up); T7 increased P foliar and decreased total soluble solids in juice compared with control. Foliar fertilization with macronutrients allows increased fruit production of 'Valencia late' sweet orange and 'Murcott' tangor. This report shows the utility of the foliar nutrition with macronutrient as a tool in citrus fertilization programs designed to optimize the fruit performance.